The challenges to the emergency medical services to be recognised as a human right in international human rights law - Uusitalo, Jenna (Array, 2020)
The Emergency Medical Services (EMS) are emergency services generally been designed to provide urgent treatment of patients with life-threatening conditions outside medical facilities. Even though the EMS belongs to the category of socio-economic rights, it nevertheless has great significance in safeguarding one of the most fundamental human rights, the right to life. In fact, international humanitarian law has recognised this important connection by establishing explicit legal rules that oblige states to ensure urgent medical care for the wounded and sick. International human rights law, on the other hand, has no such expressed provisions. However, the problem is not the lack of legal rules applicable to the EMS as such but rather the challenges in human rights perception, which hinder the EMS being perceived as a valuable human right. Therefore, this article essentially argues that international human rights law does not recognise the EMS as a human right sufficiently and that more thorough actions are required from the UN Committee of Economic, Social and Cultural Rights (CESCR) in this regard.